Impact of Manufactured Exports on Economic Growth in ASEAN - Lustari Agustin; Faiza Husnayeni Nahar (Universitas Muhammadiyah Yogyakarta, 2020)
Economic growth is an essential factor to measure how prosperous the economy of a country is. Therefore, each country will always try to increase their economic growth and put it as its economic target. This research aimed to find out the factors that influence the economic growth in ASEAN member countries during 2007–2016. The analysis method used was Generalized Least Square (GLS) method and Fixed Effect Estimation model. The data used were the panel data of seven ASEAN countries. The result showed that Manufacturing Export, Foreign Direct Investment (FDI), Government Expenditure, and Population had a positive and significant effect on economic growth although the contribution of manufacturing export is just at a small magnitude.